PENDIDIKAN MULTIKULTURAL DALAM PENDIDIKAN ISLAM DAN URGENSINYA DI INDONESIA - Syamsul Rijal (Fakultas Agama Islam Universitas Islam Madura, 2021)
Multicultural education was born in different parts of the world not in a vacuum, it was born because of the reality of multiculturalism that should exist. A struggle for equality and equality, democracy and human rights. The process of democratization usually requires recognition of human rights that do not distinguish human differences over skin color, religion, customs, culture or gender. The concept of multicultural education within the framework of Islamic education, can be realized with a long and continuous business process and efforts. Both are highly relevant and accommodating to issues of pluralism and democracy. This can be traced from the basic principles of multicultural education and Islamic education which are very relevant. Both are highly regarded for human rights and have a strong commitment to realize it. The implementation of multicultural Islamic education can be realized not only in the realm of formal education an-sich, it can take place in non-formal education, family and the wider community. Of course, with a long and sustainable process in addition to the improvement and preparation of a more comprehensive system in the curriculum, infrastructures, learning models to the competence of educators must be adapted to these ideals. Indonesia as a country that has a variety of cultural people in building national and state life needs to develop education that has multicultural insight. Through the principle of